The promising role of miRNAs in radioresistance and chemoresistance of nasopharyngeal carcinoma - Xu, Haoyuan; Li, Wanpeng; Wang, Dehui (Frontiers in Oncology, 2024)
Nasopharyngeal carcinoma (NPC) is a very common malignant epithelial tumorcy that occurs develops 1 in the nasopharynx. It has a distinct ethnic and geographical distribution, . and emerging evidence suggests that it is an ecological disease. Most patients respond greatlywell to radiationradiation coupled combined with chemotherapy as the primary treatment for NPC. However, certainsome patients will eventually develop radioresistance and chemoresistance, resulting in recurrence and metastasis, which is a primarymajor cause of poor prognosis. The processes underlying rRadioresistance and chemoresistance mechanisms in NPC are complicatedcomplex and unknown. MicroRNAs (miRNAs) related toare a type of endogenic non-coding RNA molecules. They play a role in a variety of are involved in diverse cell activities functions and as well as development of disease like such as cancer.There has been enormous considerable evidencedata manifesting demonstrating the existence of severalnumerous aberrant miRNAs in cancer tissues, cells, and biofluids, which indicates the importance of studying the influence of miRNAs on NPC. clinically. Therefore, this review comprehensively analyzes the elaborate mechanisms of miRNAs affecting the radioresistance and chemoresistance of NPC. Multiple tumor-specific miRNAs can be employed as treatment therapeutic and prognosticis biological markersindicators.